Shirley & Jamila save their summer - Goerz, Gillian (New York : Dial Books for Young Readers, 2020)
When ten-year-olds Shirley and Jamila meet, Jamila is simply hoping for a friend in her new neighborhood but Shirley is a detective and together they seek a missing gecko.
School Library Journal, June 2020
3-6.
3.4.
OBOB Elementary 2022-2023.
Keywords: Friendship -- Comic books, strips, etc -- Juvenile fiction; Lost articles -- Comic books, strips, etc -- Juvenile fiction; Detective and mystery stories; Friendship -- Fiction; Lost and found possessions -- Fiction; Mystery and detective stories; Cartoons and comics; Detective and mystery comics; Graphic novels; Comics (Graphic works).